Effect of precipitating agent, N2 gas, extract volume and pH on the magnetic properties of magnetite nanoparticles by green synthesis from aqueous pomegranate peel extract - Dehghani, Marzieh; Hajipour-Verdom, Behnam; Abdolmaleki, Parviz (Frontiers in Chemistry, 2024)
Superparamagnetic nanoparticles (SPMNPs) have attracted considerable attention in biomedicine, particularly magnetic hyperthermia for cancer treatment. However, the development of efficient and eco-friendly methods for synthesizing SPMNPs remains a challenge. This study reports on a green synthesis approach for SPMNPs using pomegranate peel extract as a stabilizing agent. The effects of various synthesis parameters, including the type of precipitating agent (NH3 and NaOH), N2 gas, extract volume, and pH, were systematically investigated with regard to the size, morphology, and magnetic properties of the nanoparticles. The results showed that reducing the volume of the extract increased the saturation magnetization of the nanoparticles. N2 gas was found to be essential in preventing the oxidation of the nanoparticles. The type of precipitating agent also affected the size and magnetization of the nanoparticles, with NaOH leading to the synthesis of SPMNPs with higher magnetization (~ 4 times) compared to NH3. Additionally, nanoparticles synthesized at pH 10 exhibited higher magnetization than those synthesized at pH 8 and 12. In conclusion, the optimized synthesis conditions significantly affected the magnetization and stability of SPMNPs. These nanoparticles are suitable for use in magnetic nanofluid hyperthermia applications.